2022
DOI: 10.1002/dvg.23491
|View full text |Cite
|
Sign up to set email alerts
|

Development and regeneration of periodontal supporting tissues

Abstract: Summary Periodontal tissues, including gingiva, cementum, periodontal ligament, and alveolar bone, play important roles in oral health. Under physiological conditions, periodontal tissues surround and support the teeth, maintaining the stability of the teeth and distributing the chewing forces. However, under pathological conditions, with the actions of various pathogenic factors, the periodontal tissues gradually undergo some irreversible changes, that is, gingival recession, periodontal ligament rupture, per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 102 publications
(135 reference statements)
0
2
0
Order By: Relevance
“…36 On the other hand, cementoblast precursors are not related or similar to osteoblasts. 37 Thus, future studies are needed to verify the relationship between metabolic reprogramming and cementoblast mineralization. Here, we have confirmed that the glucose metabolism was vigorous during cementum formation in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 On the other hand, cementoblast precursors are not related or similar to osteoblasts. 37 Thus, future studies are needed to verify the relationship between metabolic reprogramming and cementoblast mineralization. Here, we have confirmed that the glucose metabolism was vigorous during cementum formation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoblasts are found on the alveolar bone side of the periodontal ligament tissue, while cementoblasts are located near the root surface of the tooth 36 . On the other hand, cementoblast precursors are not related or similar to osteoblasts 37 . Thus, future studies are needed to verify the relationship between metabolic reprogramming and cementoblast mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…39 When the outermost mesenchymal cells of the apical papilla establish connections with the innermost cells of the HERS, they are induced to differentiate into odontoblasts and gradually retreat to the center of the dental papilla, secreting radicular dentin. 15,40,41 As dentin formation progresses, the dental papilla becomes confined to a smaller space and eventually forms the dental pulp. Once the very first coat of radicular dentin is formed and the tooth root begins to elongate, HERS loses its integrity but remains a network of connections during root development through localized apoptosis or epithelial-to-mesenchymal transition (EMT), and the remaining HERS cells in the PDL are called 'epithelial rests of Malassez (ERM)', which contribute to cementum regeneration.…”
Section: Spatiotemporal Morphogenesis and Cell Source Of Dental Rootmentioning
confidence: 99%
“…15,[42][43][44] Following the disintegration of the HERS, the lateral mesenchymal cells of the dental follicle acquire interaction with the radicular dentin and then differentiate into cementoblasts, forming acellular cementum and cellular cementum. 40,45 In the region of the cervical root, cementoblasts first deposit cementum on the dentin and withdraw from the progressing mineralization front so that they do not incorporate themselves into the cementum, termed acellular cementum, also known as primary cementum. In more apical and inter-radicular areas, unlike acellular cementum formation, cellular cementum, also known as secondary cementum, is secreted by cementoblasts when the tooth reaches the occlusal plane, mineralizing rapidly and occasionally embedding some cementoblasts as cementocytes.…”
Section: Spatiotemporal Morphogenesis and Cell Source Of Dental Rootmentioning
confidence: 99%
“…The dental follicle derives from the dental mesoderm, which originates from neural crest cells in early stages of mammalian development [9]. This tissue is not only involved in the development of the periodontium, but is also responsible for tooth eruption [10][11][12]. The dental follicle is collagenous tissue that is interspersed with small blood vessels.…”
Section: Introductionmentioning
confidence: 99%